The Impact of Dharar [Damage], Maslahat [Benefits] and Religiosity to Smoking Behaviour - Watni Marpaung (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2020)
There is still much debate about smoking behavior in Indonesia, some scholars declare it haram [forbidden] to smoke, but others state it is forbidden. There is still a lot of debate among Muslims regarding the maslahat [benefits] and dharar [damage] resulting from smoking. Researchers want to see the effect of maslahat, dharar [damage], and Religiosity on the smoking law. This study followed a cross-sectional design conducted by interviewing 518 Muslim youths taken using the snowball method and disseminating online questionnaires; data analysis uses SMART PLS with a CI of 95%. The results of this study showed an effect between maslahat [benefits] (p<0.001 and T=4.010), dhara (p=0.006 and T=2.744) to fatwa perspective [the view of a group of ulemas about a problem in perspective in Islamic law] and no significance between Religiosity (p=0.433 and T=0.785) to fatwa perspective. There is a significant influence between maslahat [benefits] (p<0.001 and T=4.605), dharar [damage] (p=0.0027 and T=2.218), and Religiosity (p=0.001 and T=2.596) on smoking law. The Indonesian government must be intense in socializing the maslahat [benefits] of smoking behavior and explaining that there is no benefit, so Muslim youths should consider smoking. This is by the rules of Ushul Fiqh, “the government policy is meant to maslahat [benefits] ” through the fatwa on smoking haram [forbidden] for Muslims issued by the Indonesian Ulema Council (MUI) and Muhammadiyah [Muhammadiyah is one of the islamic organization].